Point-of-Care Testing of Coagulation in Patients Treated With Non–Vitamin K Antagonist Oral Anticoagulants. Issue 10 (October 2015) - Ebner, Matthias; Peter, Andreas; Spencer, Charlotte; Härtig, Florian; Birschmann, Ingvild; Kuhn, Joachim; Wolf, Martin; Winter, Natalie; Russo, Francesca; Zuern, Christine S.; Blumenstock, Gunnar; Ziemann, Ulf; et al.
<x xml:space="preserve">Abstract</x> Background and Purpose— Specific coagulation assays for non–vitamin K antagonist oral anticoagulants (NOAC) are relatively slow and often lack availability. Although specific point-of-care tests (POCT) are currently not available, NOAC are known to affect established coagulation POCT. This study aimed at determining the diagnostic accuracy of the CoaguChek POCT to rule out relevant concentrations of rivaroxaban, apixaban, and dabigatran in real-life patients. Methods— We consecutively enrolled 60 ischemic stroke patients newly started on NOAC treatment and obtained blood samples at 6 prespecified time points. Samples were tested using the CoaguChek POCT, laboratory-based coagulation assays (prothrombin time and activated partial thromboplastin time, anti-Xa test and Hemoclot), and liquid chromatography–tandem mass spectrometry for direct determination of NOAC concentrations. Results— Three hundred fifty-six blood samples were collected. The CoaguChek POCT strongly correlated (r=0.82 P<0.001) with rivaroxaban concentrations but did not accurately detect dabigatran or apixaban. If used to estimate the presence of low rivaroxaban concentrations, POCT was superior to predictions based on normal prothrombin time and activated partial thromboplastin time values even if sensitive reagents were used. POCT-results ⩽1.0 predicted rivaroxaban concentrations <32 and <100 ng/mL with a specificity of 90% and 96%, respectively. Conclusions— If anti-Xa test is not available, we propose the use of the CoaguChek POCT to guide thrombolysis decisions after individual risk assessment in rivaroxaban-treated patients having acute ischemic stroke. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT02371044.